Direct-Write Bioprinting Approach to Construct Multilayer Cellular Tissues - Masaeli, Elahe; Marquette, Christophe (Frontiers in Bioengineering and Biotechnology, 2020)
As a cellular-assembly technique, bioprinting has been extensively used in tissue engineering and regenerative medicine to construct hydrogel-based three-dimensional (3D) tissue-like models with prescribed geometry. Here, we introduced a unique direct-write bioprinting strategy to fabricate a bilayer flat tissue in a hydrogel-free approach. A printed retina pigmented epithelium layer (RPE) was applied as living biopaper for positioning a fibroblast layer without using any hydrogel in bioink. We adjusted the number of cells in the droplets to have a uniform printed cell layer and show formation of bilayer construct with confocal imaging. Since our printing system introduces low levels of shear stress to the cells, it did not have a negative effect on cell survival, although cell viability was generally lower than that of control group over one week post-printing. In conclusion, our novel direct-write bioprinting approach to spatiotemporally position different cellular layers may represent an efficient tool to develop living constructs especially for regeneration of complex flat tissues.